The relationship between the COVID-19 pandemic and the sexual life quality of nurses - Ekrem, Ebru Cirban; Erciyas, Şeyma Kilci (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. Sexuality is one of the basic human needs. The coronavirus has adversely affected every aspect of people’s lives. The nurses who were in the closest contact with the patients were affected more negatively due to the many unknowns during the COVID-19 pandemic. Aim of this study is to determine the relationship between the COVID-19 pandemic and the sexual quality of life of nurses. Material and methods. The sample of this descriptive-cross-sectional study consisted of 390 nurses who met the inclusion criteria. The data were collected over the social networks between November 2020-January 2021. The data were collected through social networks using the “Personal Information Form” and “Quality of Sexual Life Scale-Women” using the self-report method. Results. The mean age of the nurses was 32.44±6.83, and 59.2% of them had a university level education. The mean score of the women’s sexual quality of life scale was calculated as 87.37±20.83. It has been determined that there is a statistically significant difference between the scores obtained from the sexual life quality scale according to the status of the nurses having (p<0.05). Conclusion. In the COVID-19 pandemic, it was determined that the sexual life quality of nurses was above the medium level and their sexual life was adversely affected.
Keywords: COVID-19; nurse; pandemic; sexuality